Edukasi Dan Pencegahan Risiko Penyakit Terkait Kebiasaan Merokok Di Desa Sebewe - Rafi’ah Rafi’ah; Iga Maliga; Ana Lestari; Asri Reni Handayani; David Hariyanto (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
Smoking is a habit that has serious negative impacts on human health and the surrounding environment. The importance of increasing public understanding of the risks of smoking is a crucial step in the effort to prevent smoking-related diseases. The education provided should include information about harmful substances in cigarettes and their effects on the human body. The purpose of this community service activity is to enhance public awareness of the health risks associated with smoking habits. This activity involves community participation and the delivery of education door-to-door in the Sebewe village, conducted from December 2023 to January 2024. The service encompasses the entire process, from preparation to evaluation. The method used in this community service activity is a socialization method to provide information to the community regarding disease prevention and risks associated with smoking habits. Evaluation results indicate that although the community is aware of the health risks caused by smoking, their knowledge of the dangers of smoking is still low. Therefore, it is hoped that this activity will increase awareness and knowledge in the community regarding disease prevention and risks associated with the habit of smoking.